Visualization of subjective extracted text using the parse tree - Mirzabeiki, Erfan; Abdullah, Lili Nurliyana (Research and Publication Unit, University of Asia Pacific, 2014)
Text visualization is a well-known technique used in note taking and obviating the difficulties of the learners in focusing on important portions of the text materials to be learnt. On the other hand applying the text visualization methods on the extracted sections required by the learners will amplify the efficiency of perceiving from the text. This paper intends to propose an automatic approach for subjective extracted text visualization to improve leaning from digital text. The main function of this approach divided into two parts, firstly: sentence extraction based on the inclusion of a significant part of speech and role of the words in sentence (i.e. Noun/Names/Places/dates Numbers/ Events) by using the parse tree, secondly: Visualization of the extracted information for maintaining the user’s attention on the content were developed on the basis of psychological, multimedia, and typographic cueing foundations and techniques (visual effects). This experiment conducted on different sample texts in the field of “History” in order to visualize the extracted part.